2002
DOI: 10.1097/00006842-200201000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy Impacts Self-Care and HbA1c in Young Adults With Type I Diabetes

Abstract: Self-efficacy is an important factor for management of self-care practices and physiological outcomes among young adults with Type I diabetes, and self-care may be an important mechanism by which self-efficacy influences HbA1c levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
127
1
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(144 citation statements)
references
References 35 publications
13
127
1
3
Order By: Relevance
“…1. Tables 1 and 2, and the Electronic supplementary material (ESM Table 1), detail the papers that were included in (n=14) [27][28][29][30][31][32][33][34][35][36][37][38][39][40] and excluded from (n=11) the review. There were 16 relationships between psychosocial measures and disease-related factors in populations with diabetes and six relationships between psychosocial measures and diseaserelated factors in populations without diabetes at baseline.…”
Section: Resultsmentioning
confidence: 99%
“…1. Tables 1 and 2, and the Electronic supplementary material (ESM Table 1), detail the papers that were included in (n=14) [27][28][29][30][31][32][33][34][35][36][37][38][39][40] and excluded from (n=11) the review. There were 16 relationships between psychosocial measures and disease-related factors in populations with diabetes and six relationships between psychosocial measures and diseaserelated factors in populations without diabetes at baseline.…”
Section: Resultsmentioning
confidence: 99%
“…Self-efficacy and selfregulation may be useful psychological constructs for understanding the ways one addresses self-care (22,23). However, only two studies have investigated selfefficacy and the insulin pump with adolescents (24,25), and no studies on selfregulation and the insulin pump have been reported.…”
Section: Body Image and Social Acceptancementioning
confidence: 99%
“…The role of self-efficacy in self-management behaviors has been examined in studies on back pain [20]; arthritis [21]; heart disease [22] and diabetes [23]. These studies found that patients who maintained high levels of self-efficacy and possessed positive attitudes toward self-management behaviors were more likely to perform those behaviors.…”
Section: Introductionmentioning
confidence: 99%